The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1292/jvms.18-0083
|View full text |Cite
|
Sign up to set email alerts
|

Development of PCR for identifying <i>Streptococcus parasuis</i>, a close relative of <i>Streptococcus suis</i>

Abstract: Streptococcus parasuis has recently been removed taxonomically from Streptococcus suis, a zoonotic pathogen. S. parasuis has been detected in healthy pigs and in diseased pigs, which suggests that S. parasuis is involved in the normal microbiota of pigs and has potential pathogenicity. However, the pathogenicity of S. parasuis in pigs is unclear because of the lack of appropriate detection methods that discriminate S. parasuis from S. suis. In this study, we developed a PCR method that is specific for S. paras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…orisratti , and 1 S . ruminantium strains [23]; and (iv) 16S rRNA gene sequences of 4,596 streptococcal strains in the RDP (last accessed in January 2016). These sequences were dereplicated using Cluster Database at High Identity with Tolerance (CD-HIT) program [24] with the sequence identity threshold of 1.0, and were finally clustered into 909 groups.…”
Section: Methodsmentioning
confidence: 99%
“…orisratti , and 1 S . ruminantium strains [23]; and (iv) 16S rRNA gene sequences of 4,596 streptococcal strains in the RDP (last accessed in January 2016). These sequences were dereplicated using Cluster Database at High Identity with Tolerance (CD-HIT) program [24] with the sequence identity threshold of 1.0, and were finally clustered into 909 groups.…”
Section: Methodsmentioning
confidence: 99%
“…The two strains were confirmed as not belonging to S. suis by amplifying a nearly complete 16S rRNA gene using primer 27F(5′-AGAGTTTGATCMTGGCTCAG-3″) and 1492R (5′-TACGGYTACCTTGTTACGACTT-3′) and S. suis –specific recN and gdh genes [ 31 , 32 , 33 , 34 ]. Data of 16S rRNA sequencing and the PCR method detecting recN gene specific to S. parasuis [ 6 ] indicated that the two strains belonged to the S. parasuis species.…”
Section: Methodsmentioning
confidence: 99%
“…S. suis serotypes 32 and 34 have been reclassified as Streptococcus orisratti [4]. Recently, S. suis reference strains of serotypes 20, 22, 26 were proposed as Streptococcus parasuis [5] and serotype 33 was reclassified as Streptococcus ruminantium [6]. The presence of S. parasuis in diseased pigs and calves with pneumonia or systemic infection (meningitis, arthritis, endocarditis, or septicemia) indicated that S. parasuis may be pathogenic to pigs and/or calves [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…It is closely related to S. suis but can be distinguished from it based on genetic content and biochemical features, such as the absence of both β-galactosidase activity and arginine hydrolyses (1, 2). Strains can easily be classified as S. parasuis based on a positive PCR targeting a 679-bp fragment near the recN gene (2).…”
Section: Announcementmentioning
confidence: 99%
“…Until now it was unclear whether S. parasuis is a pathogen, like its close relative S. suis, or whether it is a member of the commensal microbiota of pigs (2).…”
Section: Announcementmentioning
confidence: 99%